Chemical profile of phenolic compounds in wheat pasta supplemented with chia - Pigni, Natalia (2017)
Fil: Pigni, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencia y Tecnología de los Alimentos Córdoba; Argentina.